Per Jacobsson Lecture : Are We Safer? The Case for Strengthening the Bagehot Arsenal - Geithner, Timothy (Washington, D.C. : International Monetary Fund, 2017)
The choices we make in advance of the next financial crisis will have a major impact in determining the magnitude of the economic damage. Our vulnerability to crisis depends on the strength of the protections we build into the financial system through prudential regulation, as well as on the degrees of freedom we create for ourselves to respond to the unanticipated, and the knowledge and experience we bring in managing crises. Is the financial system safer today? With the reforms now in place and with the memory of the crisis still fresh, how confident should we feel about the resilience of the financial system and our ability to protect the US economy from a major financial crisis? Warburg Pincus President and former US Secretary of the Treasury Timothy Geithner attempts to answer these questions in his October 2016 Per Jacobsson Lecture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet